Analysis of electroosmotic characters in fractal porous media. (4th May 2015) - Liang, Mingchao; Yang, Shanshan; Miao, Tongjun; Yu, Boming
Abstract: Electroosmotic flow (EOF) in porous media has very important applications in various scientific and engineering fields. In this article, a fractal model for the height difference caused by the EOFs in porous media is developed based on the fractal theory of porous media and on the electrokinetic flow in capillaries, whose tortuosity is taken into account. The proposed model indicates that the height difference is a function of the physical properties of electrolyte solutions, micro-structural parameters of porous media, zeta potential on the solid surface and Debye thickness near the solid–liquid interface in porous media. Factors influencing the height difference are also analyzed. The model predictions show the same variation tendencies with the available experimental data reported in literature. It is found that the proposed fractal model is superior to the hydraulic radius model in terms of dealing with transport in porous media. Highlights: Fractal model for the height difference caused by the EOFs in porous media is built. Fractal model predictions are in good agreement with the experimental data. Factors influencing the height difference are discussed and analyzed in detail.